A parsimonious model to achieve high customer retention in Singapore’s highly competitive takeaway food business sector. - Leong, Wei Jie. (2010)
Takeaway food is gaining popularity, especially in a fast-paced modern society such as Singapore. Many new takeaway food businesses have emerged, but few have managed to survive long in this competitive sector. Our research revealed that with a huge amount of choices available to the consumer, customer retention is crucial as firms cannot merely depend on acquiring new customers for long term survivability and sustainability. The objective of this research is to achieve a strong understanding of the factors affecting customer retention in the takeaway food sector. Through our first interview and literature review, we identified the factors of Service Quality, Product Quality, Trust, Locational Convenience and Customer Satisfaction as being most important, and proceed to study their effects on customer retention through a combination of qualitative and quantitative research methods. Our findings reveal that with the exception of Customer Satisfaction, the factors of Service Quality, Product Quality, Trust and Locational Convenience were all significant factors of customer retention. Trust is found to have the strongest influence on customer retention, and is often cited by our interviewees to be the result of consistent Product Quality, Service Quality and Locational Convenience offered by the takeaway food establishment. These 4 factors were then synthesized into the overarching theme of Consistent Quality. In conclusion, managers of takeaway food businesses should focus on providing pre-determined desired standards in all three areas of food, service and location consistently to each customer, across all outlets and at all times. This will help foster customer’s trust in the quality offered by the takeaway food business, and allow the business to achieve the concept of Consistent Quality, which is ultimately the key to achieving high customer retention.